Fission stories: using PomBase to understand Schizosaccharomyces pombe biology. Issue 4 (23rd December 2021) - Harris, Midori A; Rutherford, Kim M; Hayles, Jacqueline; Lock, Antonia; Bähler, Jürg; Oliver, Stephen G; Mata, Juan; Wood, Valerie
Abstract: PomBase (www.pombase.org ), the model organism database (MOD) for the fission yeast Schizosaccharomyces pombe, supports research within and beyond the S. pombe community by integrating and presenting genetic, molecular, and cell biological knowledge into intuitive displays and comprehensive data collections. With new content, novel query capabilities, and biologist-friendly data summaries and visualization, PomBase also drives innovation in the MOD community.